Tumour catabolism independent of malnutrition and inflammation in upper GI cancer patients revealed by longitudinal metabolomics. Issue 1 (23rd November 2022) - von Renesse, Janusz; von Bechtolsheim, Felix; Jonas, Sophie; Seifert, Lena; Alves, Tiago C.; Seifert, Adrian M.; Komorek, Filip; Tritchkova, Guergana; Menschikowski, Mario; Bork, Ulrich; Meisterfeld, Ronny; Distler, Marius; et al.
Abstract: Background: The detrimental impact of malnutrition and cachexia in cancer patients subjected to surgical resection is well established. However, how systemic and local metabolic alterations in cancer patients impact the serum metabolite signature, thereby leading to cancer‐specific differences, is poorly defined. In order to implement metabolomics as a potential tool in clinical diagnostics and disease follow‐up, targeted metabolite profiling based on quantitative measurements is essential. We hypothesized that the quantitative metabolic profile assessed by 1 H nuclear magnetic resonance (NMR) spectroscopy can be used to identify cancer‐induced catabolism and potentially distinguish between specific tumour entities. Importantly, to prove tumour dependency and assess metabolic normalization, we additionally analysed the metabolome of patients' sera longitudinally post‐surgery in order to assess metabolic normalization. Methods: Forty two metabolites in sera of patients with tumour entities known to cause malnutrition and cachexia, namely, upper gastrointestinal cancer and pancreatic cancer, as well as sera of healthy controls, were quantified by 1 H NMR spectroscopy. Results: Comparing serum metabolites of patients with gastrointestinal cancer with healthy controls and pancreatic cancer patients, we identified at least 15 significantly changed metabolites in each comparison. Principal component and pathway analysis tools showed a catabolic signature in preoperative upper gastrointestinal cancer patients. The most specifically upregulated metabolite group in gastrointestinal cancer patients was ketone bodies (3‐hydroxybutyrate, P < 0.0001; acetoacetate, P < 0.0001; acetone, P < 0.0001; false discovery rate [FDR] adjusted). Increased glycerol levels ( P < 0.0001), increased concentration of the ketogenic amino acid lysine ( P = 0.03) and a significant correlation of 3‐hydroxybutyrate levels with branched‐chained amino acids (leucine, P = 0.02; isoleucine, P = 0.04 [FDR adjusted]) suggested that ketone body synthesis was driven by lipolysis and amino acid breakdown. Interestingly, the catabolic signature was independent of the body mass index, clinically assessed malnutrition using the nutritional risk screening score, and systemic inflammation assessed by CRP and leukocyte count. Longitudinal measurements and principal component analyses revealed a quick normalization of key metabolic alterations seven days post‐surgery, including ketosis. Conclusions: Together, the quantitative metabolic profile obtained by 1 H NMR spectroscopy identified a tumour‐induced catabolic signature specific to upper gastrointestinal cancer patients and enabled monitoring restoration of metabolic homeostasis after surgery. This approach was critical to identify the obtained metabolic profile as an upper gastrointestinal cancer‐specific signature independent of malnutrition and inflammation.